A) x + 2x + 3x = 42 B) x + y + z = 42 C) x + x/2 + x/3 = 42 D) x + x + 2 + x + 3 = 42
A) a + y + z = 61 B) x + x + 1 + x + 2 = 61 C) x + x + x = 61 D) x + 2x + 3x = 61
A) 2x B) x+x C) x2 D) x/2
A) a2 - b2 B) a2 - b C) (a - b)2 D) a - b2
A) x + x / 3 B) 3x - x / 3 C) x - x / 3 D) 3x + x / 3
A) x + 1 B) x C) 1 / x D) x2
A) c2 = a2 b2 B) c2 = a2 + b2 C) c2 = a + b D) c2 = a2 - b2
A) a + 5 B) 5 - a C) 5a D) a - 5
A) (a + b) - (a - b) B) (a + b) / (a - b) C) (a + b)(a - b) D) (a + b) + (a - b)
A) 2xy B) -2xy C) 2x - y D) x - 2y
A) x / y = 45 B) 2x + y = 45 C) x + y = 45 D) xy = 45
A) A = (b -h) / 2 B) A = bh / 2 C) A = 2(b +h) D) A = (b +h) / 2
A) 2x B) x2 C) x - 2 D) 2 + x
A) (x + y + z) / 3 B) 3(x + y + z) C) x + 2y + 3z D) (x - y - z) / 3
A) P = a2 B) P = 4a2 C) P = 4a D) P = 4 - a
A) n - 3 B) 3n3 C) 3n D) n3
A) (x + y)(x - y) B) xy C) (x+y) - (x - y) D) x(x - y)
A) a - 3b B) 3(a - b) C) (a - b)3 D) 3a - b
A) x3 = 19 B) x - 3 = 19 C) x + 3 = 19 D) 3x = 19
A) gf B) g + f C) g - f D) g / f
A) hk B) h - k C) h + k D) h / k
A) b + +c B) bc C) b / c D) b - c
A) (2abc)2 B) (abc)2 C) (abc)4 D) 2(abc)2 |